Molecular identifcation and morphological variations of Dermacentor albipictus collected from two deer species in northern Mexico - Escarcega Avila, Angelica Maria (2021)
In total, 57 ticks were collected from six white-tailed deer (Odocoileus virginianus) and three mule deer (O. hemionus) in northern Mexico during the 2017, 2018 and 2019 hunting seasons. Morphological features of adult male and female ticks were observed and photographed using a stereo-microscope and scanning electron micrography. The ticks were identifed as Dermacentor albipictus based on taxonomic keys. Molecular analysis using DNA amplifcation of the 16S rDNA and cytochrome oxidase 1 (COI) genes was employed to resolve the phylogenetic relationships from 18 strains of Dermacentor species. Bayesian phylogenetic analysis was performed in order to obtain a phylogenetic tree based on the concatenated sequence in the D. albipictus clade. The geometric morphometric analysis compared the body shape of ticks collected from specimens of two deer species by analyzing nine dorsal and ventral landmarks from both males and females. The results suggest that body shape variation in dorsal structures might be related to the host.